Inflammation, Sepsis, and the Coagulation System - Kappelmayer, János; Debreceni, Ildikó Beke; Fejes, Zsolt; Nagy, Béla, Jr. (Hämostaseologie, 2024)
Sepsis has been a major health problem for centuries and it is still the leading cause of hospital deaths. Several studies in the past decades have identified numerous biochemical abnormalities in severe cases, and many of these studies provide evidence of the perturbation of the hemostatic system. This can result in complications, such as disseminated intravascular coagulation that can lead to multiorgan failure. Nevertheless, large clinical studies have demonstrated that the simple approach of inhibiting the coagulation processes by any means fails to provide significant improvement in the survival of septic patients. A cause of this failure could be the fact that in sepsis the major clinical problems result not primarily from the presence of the infective agent or enhanced coagulation but from the complex dysregulated systemic host response to pathogens. If this overt reaction is not fully deciphered, appropriate interference is highly unlikely and any improvement by conventional therapeutic interventions would be limited. Cellular activation in sepsis can be targeted by novel approaches like inhibition of the heterotypic cellular interactions of blood cells by targeting surface receptors or posttranscriptional control of the hemostatic system by noncoding ribonucleic acid (RNA) molecules. Stable RNA molecules can affect the expression of several proteins. Thus, it can be anticipated that modulation of microRNA production would result in a multitude of effects that may be beneficial in septic cases. Here, we highlight some of the recent diagnostic possibilities and potential novel routes of the dysregulated host response.
Keywords: sepsis; inflammation; biomarker; p-selectin; procoagulant platelets; microRNAs